Factors affecting the prioritization of the most important construction violations in the article 100 commission: Case study of Yasuj city - Ameneh Fatehipoor; Ali Aram (مهندسی و مدیریت ساخت)
The basis and reference for investigating construction violations within the legal framework and approved by cities is Article 100 of the Municipalities Law and its 11 notes. Despite the penalties provided for in Article 100 of the Iranian Municipal Law for such violations, it does not appear to be effective. The purpose of this study was to investigate the factors affecting the prioritization of the most important construction violations in the Article 100 Commission (case study of Yasuj city). This research was a descriptive survey in terms of practical purpose and data collection in terms of data collection and data collection tool in this field research was a questionnaire. The statistical population of this research is the members of Yasuj Building Engineering System Organization. Morgan's table was used to estimate the sample size, which is equal to 100 people. Research data were analyzed using hierarchical method. AHP method was used to analyze the data and test the main research hypothesis. Data were collected using a questionnaire and analyzed by Expert Chice software. The results showed that the most important factors in prioritizing the most important construction violations in the Article 100 Commission (case study of Yasuj city) from the strongest to the weakest factors are: violation of construction against the use of the building (23%), lack of strength ( 21%), non-observance of technical principles (17%), encroachment on urban thoroughfares (14%), violation of unlicensed building (8%), violation of non-construction of parking (7%), violation of building density (6%), engineer violations Observer (4%).